Amygdala network reorganization mediates the theory of mind performances in multiple sclerosis. Issue 2 (19th November 2021) - Koubiyr, Ismail; Dulau‐Metras, Cécile; Deloire, Mathilde; Charré‐Morin, Julie; Saubusse, Aurore; Brochet, Bruno; Ruet, Aurélie
Abstract: Theory of mind (ToM) seems to be affected in multiple sclerosis (MS). MRI studies suggested a role of the amygdala in social cognitive performances. Therefore, we explored the role of the amygdala network in ToM using a multimodal MRI approach. In MS, patients with impaired ToM showed contradictory dysexecutive neuropsychological profile. Therefore, we compared neural networks involved in ToM and executive functions (EFs). Twenty patients with relapsing‐remitting MS and 15 matched healthy controls were selected. ToM (Faux Pas test and mind stories) and EFs were assessed within and outside the scanner. All subjects underwent a battery of neuropsychological tests. Multimodal MRI with structural (diffusion imaging) and functional (resting‐state and task‐based) sequences was used to analyze the role and connections of the amygdala in ToM functioning. Cognitive and ToM performances were similar between patients and controls. Resting‐state data revealed decreased connectivity of the left amygdala with frontal areas in patients compared to controls ( p  < 0.0001). During the task‐based functional MRI, patients demonstrated increased connectivity between the amygdala and several cerebellar and left temporal regions (all p  < 0.05). The microstructural alterations between the left amygdala and left temporal regions were associated with increased functional connectivity within the same pathway ( r  = 0.74; p  < 0.01). No overlap was observed between functional networks involved in ToM and EFs. Our study demonstrates more connectivity recruitment between the amygdala and cerebellar and temporal regions in MS patients to reach preserved ToM performance. Microstructural abnormalities have been related to this compensatory network. Finally, different networks were involved in EFs and ToM. Abstract : In our study, patients with multiple sclerosis demonstrated preserved performances in theory of mind. Using a multimodal MRI approach, we demonstrated more connectivity recruitment between the amygdala and cerebellar and temporal regions in patients. Structural connectivity abnormalities have also been related to this compensatory mechanism.